Female genital mutilation/cutting: Emerging factors sustaining medicalization related changes in selected Kenyan communities. - Samuel Kimani; Caroline W Kabiru; Jacinta Muteshi; Jaldesa Guyo (PLoS ONE, 2020)
Although female genital mutilation/cutting (FGM/C) has declined, it is pervasive albeit changing form among communities in Kenya. Transformation of FGM/C include medicalization although poorly understood has increased undermining abandonment efforts for the practice. We sought to understand drivers of medicalization in FGM/C among selected Kenyan communities. A qualitative study involving participants from Abagusii, Somali and Kuria communities and key informants with health care providers from four Kenyan counties was conducted. Data were collected using in-depth interviews (n = 54), key informant interviews (n = 56) and 45 focus group discussions. Data were transcribed and analyzed thematically using NVivo version 12. We found families practiced FGM/C for reasons including conformity to culture/tradition, religion, marriageability, fear of negative sanctions, and rite of passage. Medicalized FGM/C was only reported by participants from the Abagusii and Somali communities. Few Kuria participants shared that medicalized FGM/C was against their culture and would attract sanctions. Medicalized FGM/C was perceived to have few health complications, shorter healing, and enables families to hide from law. To avoid arrest or sanctions, medicalized FGM/C was performed at home/private clinics. Desire to mitigate health complications and income were cited as reasons for health providers performing of FGM/C. Medicalization was believed to perpetuate the practice as it was perceived as modernized FGM/C. FGM/C remains pervasive in the studied Kenyan communities albeit changed form and context. Findings suggest medicalization sustain FGM/C by allowing families and health providers to conform to social norms underpinning FGM/C while addressing risks of FGM/C complications and legal prohibitions. This underscores the need for more nuanced approaches targeting health providers, families and communities to promote abandonment of FGM/C while addressing medicalization.